Modified positive electrode material for sodium battery and preparation method of modified positive electrode material
Through the preparation of the coated active material, the problem of poor electrochemical performance of the positive electrode material of sodium ion battery is solved, and the good cycle stability and capacity retention of sodium batteries at high magnifications are achieved, which expands its application range.
Patent Information
- Application Number
- CN202510208861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrochemical performance of the positive electrode material of sodium ion battery is poor, resulting in the limitation of the practical application of sodium ion battery.
The coated active material is used as the positive electrode material, and the sodium, manganese and copper sources are mixed with the porous polymer material through mechanical stirring and sonication to form an intermediate, and then calcined and coated with polypyrrole to prepare a positive electrode material with excellent conductivity and structural stability.
It improves the conductivity and cycle stability of the positive electrode material of sodium battery, enhances the rate performance and capacity retention rate, and broadens the application range of sodium batteries.
Smart Images

Figure CN119695128A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium batteries, and in particular to a modified positive electrode material for a sodium battery and a preparation method thereof. Background Art
[0002] People's daily production activities and life needs all require energy consumption. Energy is a powerful driving force for social development. For a long time, fossil fuels have dominated the energy supply. However, human beings' excessive dependence on and use of fossil fuels have caused irreversible damage to the natural environment. At the same time, limited fossil fuel reserves and growing energy demand have led to a serious energy crisis. Therefore, the development of pollution-free, renewable green energy is imminent. In recent years, with the development of renewable energy, emerging energy storage systems have received widespread attention. Among them, lithium-ion batteries are the largest electrochemical energy storage technology currently used. However, the content of lithium in the earth's crust is extremely small. Continuous mining and use will eventually lead to the depletion of lithium elements, and the cost is high, which is not conducive to the continued promotion and use of lithium batteries. Because sodium-ion batteries have similar physical and chemical properties to lithium-ion batteries, and sodium resources are abundant, they have lower costs and higher safety. They are potential substitutes for lithium-ion batteries and have received widespread attention in the field of electrochemical energy storage.
[0003] In sodium-ion batteries, positive electrode materials, as one of the key components, play a key role in the comprehensive performance of sodium-ion batteries. Currently, common positive electrode materials for sodium batteries mainly include Prussian blue compounds, oxides of transition metals and sodium, polyanion materials, organic molecules and polymers, etc. Among them, oxide materials of transition metals and sodium have become one of the preferred materials for positive electrode materials of sodium-ion batteries due to their high energy density, high specific capacity and operating voltage, and good electrochemical reversibility. However, the large ionic radius of sodium ions leads to slow kinetic behavior of the extraction and embedding processes, severe volume expansion, and poor electrochemical performance, which limits the practical application of sodium-ion batteries.
[0004] In the prior art, the performance of positive electrode materials for sodium batteries is improved mostly by coating, doping, etc. For example, the patent with announcement number CN116936781B discloses a positive electrode material for sodium ion batteries and its coating modification method, and a sodium ion battery. The invention obtains a coated and modified positive electrode material by plasma fluorination treatment of carbon nanohorns. The carbon nanohorns are used as carbon materials. Compared with other carbon materials such as graphite, the curvature structure at one end of the carbon nanohorns is conducive to the formation of fluorine-carbon semi-ionic bonds, thereby improving the discharge voltage and power density. The carbon nanohorns themselves have excellent conductivity, ultra-high specific surface area, electromagnetic properties, thermal stability, etc., which can improve the electrochemical activity and charge transfer performance of the positive electrode materials, thereby improving the specific capacity of the battery. The coating layer can isolate the positive electrode material from direct contact with the electrolyte, avoid corrosion and failure of the positive electrode material, and effectively improve the cycle stability of the battery. Based on this, the performance of the positive electrode material of the sodium ion battery can be improved by coating. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a modified positive electrode material for sodium battery and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a modified positive electrode material for a sodium battery, wherein the positive electrode material comprises the following raw materials in parts by weight: 80 to 90 parts of a coated active material, 5 to 15 parts of a conductive agent carbon black, and 10 to 20 parts of polyvinylidene fluoride;
[0008] The production method comprises the following steps:
[0009] The coated active material, conductive agent carbon black and polyvinylidene fluoride are put into N-methylpyrrolidone solvent, and mechanically stirred at a stirring rate of 300 to 500 r / min to form a uniform paste to obtain a positive electrode material.
[0010] Furthermore, the method for preparing the coated active material comprises the following steps:
[0011] S1: Mix a sodium source aqueous solution with a concentration of 0.05-0.15 mol / L, a manganese source aqueous solution with a concentration of 0.04-0.06 mol / L, and a copper source aqueous solution with a concentration of 0.04-0.06 mol / L, and mechanically stir them at a stirring rate of 100-300 r / min to obtain a mixed solution, and then add the porous polymer material to the mixed solution. After the addition is completed, the system temperature is increased to 50-60°C, ultrasonic treatment is performed for 4-8 hours, and the material is separated and collected to obtain an intermediate;
[0012] S2: placing the intermediate in a tubular furnace for calcination, cooling and discharging the material to obtain an active material;
[0013] S3: The active material is mixed with deionized water to form a uniform dispersion, pyrrole monomer and dopant are added to the dispersion, stirring is continued, and then an aqueous solution of ferric chloride is added, mechanical stirring is performed for 6 to 10 hours, and solid materials are separated by filtration. After washing and drying, the coated active material is obtained.
[0014] Furthermore, in step S1, the sodium source is any one of sodium nitrate, sodium chloride or sodium oxalate; the manganese source is any one of manganese nitrate, manganese chloride or manganese acetate; the copper source is any one of copper chloride, copper acetate or copper nitrate.
[0015] Furthermore, in step S1, the ultrasonic frequency in the ultrasonic treatment is 100-200 kHz.
[0016] Furthermore, in step S2, the calcination temperature is 600-800°C and the time is 3-5 hours.
[0017] Furthermore, in step S3, the dopant is sodium dodecyl sulfate.
[0018] It can be inferred that the principle of the above scheme is: in step S1, the sodium source, manganese source and copper source will ionize metal cations in the aqueous solution, and the porous polymer material is negatively charged in the aqueous solution, so there is electrostatic adsorption between them. In addition, the porous polymer material contains a large number of carboxyl groups, which can complex with the ionized metal cations, so that under the action of electrostatic adsorption, complexation and ultrasound, the metal cations will stably adhere to the porous polymer material to obtain an intermediate; in step S2, the intermediate is carbonized after calcination treatment, and the metal cations can be oxidized into oxides in the air to obtain an active material; in step S3, under the action of the dopant and the ferric chloride aqueous solution, the pyrrole monomer can be induced to undergo an in-situ polymerization reaction on the surface of the active material, so that the polypyrrole is coated on the surface of the active material to obtain a coated active material.
[0019] Furthermore, the method for preparing the porous polymer material comprises the following steps:
[0020] Add N,N-dimethylallylamine, itaconic acid and divinylbenzene into a reaction kettle, mix well, add initiator and Span 80, ultrasonically disperse for 5 to 10 minutes, then add calcium chloride solution into the reaction kettle, continue stirring for 30 to 50 minutes, then transfer to a constant temperature water bath at 60 to 80°C and let stand for reaction for 12 to 36 hours, discharge the material, and vacuum dry to obtain a porous polymer material.
[0021] Furthermore, the initiator is azobisisobutyronitrile.
[0022] Furthermore, the concentration of the calcium chloride solution is 0.1-0.5 mol / L.
[0023] It can be inferred that the principle of the above scheme is: using N,N-dimethylallylamine and itaconic acid as continuous phases, divinylbenzene as a cross-linking agent, and calcium chloride solution as a dispersed phase, a high internal phase emulsion template method is used to prepare a porous polymer material.
[0024] A modified positive electrode material for a sodium battery is made by adopting the above-mentioned manufacturing method.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention prepares a coated active material as the active material in the positive electrode material, so that the resistivity of the prepared positive electrode material is as low as 2.0Ω·m, and the material has good conductivity. The prepared sodium battery has a discharge capacity of up to 179.1mAh / g, 165.4mAh / g, and 156.4mAh / g at 1C, 3C, and 5C rates, and the discharge capacity does not decrease significantly after 50 cycles. Moreover, the capacity retention rate is as high as 96.3% after 50 cycles at 5C rate. The material has good rate performance and cycle stability, can improve the electrochemical properties of the positive electrode material, and effectively broaden the application range of the sodium battery.
[0027] (2) The present invention prepares a coated active material. On the one hand, the porous polymer material in the coated active material can form a nitrogen-doped carbon porous material after carbonization. The rich pore structure can significantly increase the specific surface area of the material, thereby providing more active sites, which is conducive to the embedding and de-embedding of sodium ions, and effectively solves the problem of slow embedding and de-embedding process due to the large radius of sodium ions. In addition, the doping of nitrogen elements can introduce rich defect structures and sodium ion active sites, effectively improving the electrochemical properties of the material such as electrical conductivity and rate performance. On the other hand, the polypyrrole in the coated active material can effectively slow down the volume change caused by the embedding and de-embedding of sodium ions, play a good buffering role, and improve the stability of the positive electrode material structure. In addition, the coating layer polypyrrole effectively enhances the conductivity of the positive electrode material, so that the positive electrode material exhibits good rate performance and cycle stability.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1 This is a scanning electron microscope image of the porous polymer material prepared in the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] 1. Preparation of coated active materials
[0034] S1: 6 ml of 0.1 mol / L sodium nitrate aqueous solution, 6 ml of 0.05 mol / L manganese nitrate aqueous solution, and 6 ml of 0.05 mol / L copper nitrate aqueous solution were mixed, and mechanically stirred at a stirring rate of 200 r / min to obtain a mixed solution, and then 0.3 g of porous polymer material was added to the mixed solution. After the addition, the system temperature was increased to 55°C, and ultrasonic treatment was performed at an ultrasonic frequency of 150 kHz for 6 hours, and the materials were separated and collected to obtain an intermediate;
[0035] S2: placing the intermediate in a tube furnace, calcining at 700°C for 4 hours, cooling and discharging to obtain an active material;
[0036] S3: 2 g of active material was mixed with deionized water to form a uniform dispersion, 0.2 g of pyrrole monomer and 0.5 g of sodium dodecyl sulfate were added to the dispersion, and the mixture was stirred evenly. Then 1.8 g of 0.8 mol / L ferric chloride aqueous solution was added, and the mixture was mechanically stirred for 8 h. The solid material was separated by filtration, and the coated active material was obtained after washing and drying.
[0037] 2. Preparation of porous polymer materials
[0038] Add 3g of N,N-dimethylallylamine, 1.8g of itaconic acid and 0.5g of divinylbenzene into the reactor, mix well, add 0.05g of azobisisobutyronitrile and 0.5g of Span 80, ultrasonically disperse for 8min, and then add 18g of 0.2mol / L calcium chloride solution into the reactor at a rate of one drop per three seconds. After the addition, continue stirring for 40min, then transfer to a constant temperature water bath at 70°C and let it stand for reaction for 24h, discharge the material, and vacuum dry to obtain a porous polymer material.
[0039] The morphology of porous polymer materials was analyzed using an EVO 18 scanning electron microscope. The test results are shown in Figure 1 ,from Figure 1 It can be observed that the surface of the porous polymer material has a rich pore structure.
[0040] 3. Preparation of positive electrode materials
[0041] 80 g of coated active material, 5 g of conductive carbon black, and 10 g of polyvinylidene fluoride were put into N-methylpyrrolidone solvent, and mechanically stirred at a stirring rate of 300 r / min until a uniform paste was formed to obtain a positive electrode material.
[0042] Example 2
[0043] Preparation of cathode materials
[0044] 85 g of coated active material, 10 g of conductive agent carbon black, and 15 g of polyvinylidene fluoride were put into N-methylpyrrolidone solvent, and mechanically stirred at a stirring rate of 400 r / min until a uniform paste was formed to obtain a positive electrode material.
[0045] The preparation method of the coated active material is the same as that in Example 1.
[0046] Example 3
[0047] Preparation of cathode materials
[0048] 90 g of coated active material, 15 g of conductive agent carbon black, and 20 g of polyvinylidene fluoride were put into N-methylpyrrolidone solvent, and mechanically stirred at a stirring rate of 500 r / min until a uniform paste was formed to obtain a positive electrode material.
[0049] The preparation method of the coated active material is the same as that in Example 1.
[0050] Comparative Example 1
[0051] Preparation of cathode materials
[0052] 85 g of active material, 10 g of conductive agent carbon black, and 15 g of polyvinylidene fluoride were put into N-methylpyrrolidone solvent, and mechanically stirred at a stirring rate of 400 r / min until a uniform paste was formed to obtain a positive electrode material.
[0053] The preparation method of the active material is the same as that in Example 1.
[0054] Performance Testing
[0055] (1) The positive electrode materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were ground with agate, passed through a 200-mesh sieve, and then tested for resistivity using a ST2742B powder resistivity tester to evaluate the conductive properties of the positive electrode materials. The specific test results are shown in the following table:
[0056]
[0057] From the test results in the above table, it can be seen that the resistivity of the positive electrode materials prepared in Examples 1 to 3 is less than 3Ω·m, the resistivity is low, and the conductivity is good; the active material in the positive electrode material prepared in Comparative Example 1 is not coated with polypyrrole, and the resistivity of the positive electrode material is higher than that in the embodiment, and the conductivity of the positive electrode material is poor
[0058] (2) The positive electrode materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were coated on the surface of a clean aluminum foil, respectively, and then placed in a vacuum drying oven at 100° C. for drying. After drying, the electrodes were cut into circular electrode sheets as positive electrode sheets. For the assembly of sodium ion half-cells, a sodium metal sheet was used as the negative electrode. The electrolyte was 1 mol / L NaClO4 dissolved in propylene carbonate and propylene carbonate (volume ratio of 1:1) and an additive of 5% fluoroethylene carbonate. The diaphragm was glass fiber. The cells were assembled into button cells in an argon-filled glove box. After standing at room temperature for 12 hours, the positive electrode of the assembled battery was tested by cyclic voltammetry using a CH1600D electrochemical workstation to calculate the capacity retention rate. The specific test results are shown in the following table:
[0059]
[0060] From the test results in the above table, it can be seen that the batteries prepared in Examples 1 to 3 have high discharge specific capacities at rates of 1C, 3C, and 5C, and the discharge specific capacity decreases less after 50 cycles, and the capacity retention rate at a rate of 5C is greater than 95%, which has good rate performance and cycle stability; in the battery prepared in Comparative Example 1, the active material not coated with polypyrrole is directly used as the active material of the positive electrode material. The discharge specific capacity of the battery at rates of 1C, 3C, and 5C is not as good as that of the embodiment, and the discharge specific capacity decreases more after 50 cycles, and the capacity retention rate is low at a rate of 5C, and the rate performance and cycle stability of the battery are poor. It is speculated that this may be because the structure of the positive electrode material is unstable without polypyrrole coating, resulting in a decrease in the rate performance and cycle stability of the battery.
[0061] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified positive electrode material for a sodium battery, characterized in that: The positive electrode material comprises the following raw materials in parts by weight: 80 to 90 parts of coated active material, 5 to 15 parts of conductive carbon black, and 10 to 20 parts of polyvinylidene fluoride; The production method comprises the following steps: The coated active material, conductive agent carbon black and polyvinylidene fluoride are put into N-methylpyrrolidone solvent, and mechanically stirred at a stirring rate of 300 to 500 r / min to form a uniform paste to obtain a positive electrode material.
2. The method for preparing a modified positive electrode material for a sodium battery according to claim 1, characterized in that: The method for preparing the coated active material comprises the following steps: S1: Mix a sodium source aqueous solution with a concentration of 0.05-0.15 mol / L, a manganese source aqueous solution with a concentration of 0.04-0.06 mol / L, and a copper source aqueous solution with a concentration of 0.04-0.06 mol / L, and mechanically stir them at a stirring rate of 100-300 r / min to obtain a mixed solution, and then add the porous polymer material to the mixed solution. After the addition is completed, the system temperature is increased to 50-60°C, ultrasonic treatment is performed for 4-8 hours, and the material is separated and collected to obtain an intermediate; S2: placing the intermediate in a tubular furnace for calcination, cooling and discharging the material to obtain an active material; S3: The active material is mixed with deionized water to form a uniform dispersion, pyrrole monomer and dopant are added to the dispersion, stirring is continued, and then an aqueous solution of ferric chloride is added, mechanical stirring is performed for 6 to 10 hours, and solid materials are separated by filtration. After washing and drying, the coated active material is obtained.
3. The method for preparing a modified positive electrode material for a sodium battery according to claim 2, characterized in that: In step S1, the sodium source is any one of sodium nitrate, sodium chloride or sodium oxalate; the manganese source is any one of manganese nitrate, manganese chloride or manganese acetate; the copper source is any one of copper chloride, copper acetate or copper nitrate.
4. The method for preparing a modified positive electrode material for a sodium battery according to claim 2, characterized in that: In step S1, the ultrasonic frequency in the ultrasonic treatment is 100-200 kHz.
5. The method for preparing a modified positive electrode material for a sodium battery according to claim 2, characterized in that: In step S2, the calcination temperature is 600-800°C and the time is 3-5 hours.
6. The method for preparing a modified positive electrode material for a sodium battery according to claim 2, characterized in that: In step S3, the dopant is sodium dodecyl sulfate.
7. The method for preparing a modified positive electrode material for a sodium battery according to claim 2, characterized in that: The method for preparing the porous polymer material comprises the following steps: Add N,N-dimethylallylamine, itaconic acid and divinylbenzene into a reaction kettle, mix well, add initiator and Span 80, ultrasonically disperse for 5 to 10 minutes, then add calcium chloride solution into the reaction kettle, continue stirring for 30 to 50 minutes, then transfer to a constant temperature water bath at 60 to 80°C and let stand for reaction for 12 to 36 hours, discharge the material, and vacuum dry to obtain a porous polymer material.
8. The method for preparing a modified positive electrode material for a sodium battery according to claim 7, characterized in that: The initiator is azobisisobutyronitrile.
9. The method for preparing a modified positive electrode material for a sodium battery according to claim 7, characterized in that: The concentration of the calcium chloride solution is 0.1-0.5 mol / L.
10. A modified positive electrode material for a sodium battery, characterized in that: The method according to claim 1 is used for manufacturing.
Citation Information
Patent Citations
Sodium-ion battery cathode materials and their coating modification methods, sodium-ion batteries
CN116936781B
Method for modifying nickel lithium manganese anode material for lithium ion batteries
CN103474649A
Polypyrrole-coated porous sodium manganate composite material, preparation method and application thereof
CN110504437A
Hollow carbon nanofibe-CoS2 supercapacitor electrode material and preparation method thereof
CN111599607A
Polypyrrole-coated carbon-doped sodium vanadium phosphate positive electrode material as well as preparation method and application thereof
CN114300660A